AESTHETIC EVALUATION IN THE RUSSIAN WORLDVIEW: EXPLORING BEAUTY AND UGLINESS THROUGH FACIAL SIMILES - Kabidenova, Daiana (Nazarbayev University School of Sciences and Humanities, 2025)
This study explores how beauty and ugliness are conceptualized in Russian similes that describe facial features. By analyzing these, it aims to reveal culturally embedded aesthetic ideals through figurative language. Drawing on principles from cognitive linguistics, which understand similes as reflections of conceptual thought and cultural perception rather than decorative language, this research uses data from the Russian National Corpus (RNC) to examine how facial features are subject to aesthetic judgment through comparison. The main focuses of the analysis is on identifying the most frequent targets of beauty-related evaluation (e.g., eyes, nose, cheeks, lips, face, hair, and "beautiful as..." gendered constructions), the symbolic source domains used in these comparisons, the evaluative nature of the similes (positive or negative), and the presence of gendered patterns. The core findings go to show that eyes are the most emotionally and aesthetically loaded domain, meaning the similes are praising their beauty using celestial and natural imagery while also expressing intense emotions such as fear, anger, surprise, and more. Hair is primarily evaluated in terms of texture and color, where brightness, lightness, and smoothness signify beauty, and messiness suggests ugliness. As for face, facial similes often times use humor and ridicule, and that reflects the cultural sensitivities around the symmetry. The nose stands out as a heavily stigmatized feature. It is consistently mocked through very coarse, earthy comparisons, which may suggest rigid norms around the facial acceptability. In contrast, cheeks are almost exclusively associated with positive, food related imagery that conveys vitality and femininity, while lips show a more balanced duality, with beauty and grotesqueness hinging on color and size. These patterns demonstrate how metaphorical and embodied thinking works with cultural aesthetics, and by that, grounds abstract beauty ideals in more tangible and recognizable imagery that is tied to nature, objects, other humans, and emotional expression. The study attempts to contribute to the more under explored intersection of figurative language, cultural values, and aesthetic evaluations, while also offering a linguistic lens through which societal norms around physical appearance and/or gender can be examined. It can also serve as a foundation for any future cross-cultural studies that investigate how language reflects and reinstates beauty standards in different societies and time periods.
Keywords: Type of access: Open access; Similes; Beauty; Ugliness; Corpus; Cognitive Linguistics